Clinical and Functional Evolution in Subjects with Parkinson’s Disease during SARS-CoV-2 Pandemic - Marianna Capecci; Nicolò Baldini; Francesca Campignoli; Lorenzo Pasquale Lombardo; Elisa Andrenelli; Maria Gabriella Ceravolo (Applied Sciences, 2023)
The COVID-19 pandemic has been a stress test for the population, especially for people with chronic disorders such as Parkinson’s disease (PD). In addition to public health restrictions that contrast with PD management recommendations, there were deep changes in health care delivery. This retrospective study evaluates the impact of COVID-19 on the clinical and functional evolution of a cohort of 221 PD patients consecutively referred to the Movement Disorders Center between 2018 and 2021. We analyzed the trend in motor and non-motor symptoms and functional status across years based on the Unified Parkinson’s Disease Rating Scale (UPDRS) and Non-Motor Symptom Scale (NMSS). We also compared the number of emerging complications, neurologic visits, and rehabilitation sessions per subject per year. In 2020, all primary endpoint measures worsened compared to 2019, without age, disease duration, or greater neurologic impairment explaining this outcome. Concurrently, the percentage of patients receiving neurologic visits or rehabilitation sessions reduced by 53% and 58%, respectively. The subgroup analysis of 167 subjects revealed that those who received at least one cycle of rehabilitation sessions in 2020 maintained their independence level. These findings lead to emphasizing the importance of regular monitoring and rehabilitation delivery in people with chronic neurological disorders.